Hybrid Secure Model for Securing Data in The Cloud Computing System by Combining RSA, AES and CP-ABE: نموذج هجين آمن لحماية البيانات في الحوسبة السحابية بدمج RSA وAES وCP-ABE - Zakria Mahrousa, Mahmoud Rahhal, Nairouz Alzin (Journal of engineering sciences and information technology, 2021)
The cloud healthcare system represents an important application for cloud computing, as it uses the cloud for the operations of storing patient medical data and sharing it between health care service providers and patients, making the security and privacy of e-health system data the main concern of researchers. This paper presents an integrated secure model for the healthcare system in cloud computing that achieves the security and confidentiality of data transferred through cloud computing, by combining the two algorithms AES and RSA with the access control algorithm CP-ABE in order to use the advantages of each of them, where the encryption process is done by a proposed algorithm which is based on the RSA algorithm, the XOR parameter, and the AES algorithm; the secrecy of the AES algorithm has been increased by generating a dynamic key, and the confidentiality of this key has been secured with two encryption levels, the first level using the CP-ABE algorithm and the second level using the RSA algorithm. The proposed model is characterized by meeting the requirements of access control, authentication, and verification for both the transmitter and the receiver, and the results of the application of this model proved its ability to meet the security requirements of the health care system in cloud computing with the lowest possible implementation time, as the execution times were at the transmitter’s end (43.2, 43.83, 45.11, 48. 23, 50.77, 52.16, 57.95, 63.2, and 63.35)ms for variable file sizes (37, 50, 100, 150, 200, 256, 512, 1000, and 1024)KB, respectively. The results also showed its superiority in terms of security requirements in cloud computing and the necessary implementation times on studied reference models.